2022
DOI: 10.4103/sja.sja_723_21
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided sacral multifidus plane block for sacral spine surgery

Abstract: Sacral surgeries are a relatively rare type of spine surgery associated with a significant amount of perioperative pain. The paraspinal interfascial or erector spinae plane block is currently being practiced with promising results in cervical, thoracic, and lumbar spine surgeries. It provides not only effective analgesia but also helps in reducing perioperative opioid consumption. Sacral multifidus plane block is one such variant of paraspinal blocks, which may have an equianalgesic profile. This case report d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…performed the intermediate approach in the sacral spine surgery and observed selective sensory loss in the L4-S3 dermatomes postoperatively [11]. Piraccini The major limitation of this study was the implementation of the ESPB on embalmed cadavers.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…performed the intermediate approach in the sacral spine surgery and observed selective sensory loss in the L4-S3 dermatomes postoperatively [11]. Piraccini The major limitation of this study was the implementation of the ESPB on embalmed cadavers.…”
Section: Discussionmentioning
confidence: 97%
“…[10]. Mistry et al reported a case of ultrasound-guided sacral multi dus plane block for spine surgery, they performed a block bilaterally between the median and intermediate crests at S2 level [11].…”
Section: Introductionmentioning
confidence: 99%
“…We assess that the difference between our study results is due to the difference in the methods of both studies. Mistray et al performed the intermediate approach in the sacral spine surgery and observed selective sensory loss in the L4-S3 dermatomes postoperatively [11]. Piraccini et al perform the sacral ESPB with an intermediate approach unilaterally, from the S1 level, with a 15 cc drug, and the radicular pain numerical rating scale of the patient was decreased after 20 minutes, and the patient was able to stand up and walk [8].…”
Section: Discussionmentioning
confidence: 99%
“…In the same year, Aksu and Gürkan reported effective postoperative analgesia in a pediatric patient who underwent hypospadias surgery by performing the median sacral ESPB from the median sacral crest [5]. There are successful case reports of both techniques reported in the literature [6][7][8][9][10][11] The current literature includes both median and intermediate ESPB implementations. However, there is no anatomical and radiological study in the literature describing the application and the method of the median (midline) and intermediate ESPB practices.…”
Section: Introductionmentioning
confidence: 99%
“…In the same year, Aksu and Gürkan [5] reported adequate postoperative analgesia in a pediatric patient who underwent hypospadias surgery using the median approach to the SESPB, from the median sacral crest. There are radiological, anatomical, or clinical studies of SESPB in the current literature, but there is no anatomical and radiological study comparing the two methods of SESPB [6][7][8][9][10][11]. The present cadaveric study aimed to determine the distribution of local anesthesia with the median and intermediate SESPB approaches.…”
Section: Introductionmentioning
confidence: 96%